(untitled) (European Journal of Formal Sciences and Engineering, 2023)
In the 21st century, major changes have taken place in supply chain management. First of all, some new type of supply chains has appeared beside the traditional supply chains. The growing level of pollution, the decreasing level of non-renewable sources indicate changes in the business life. Companies find some alternate solutions to protect the environment – use renewable sources, integrate recycling processes, use the inverse logistics etc. So companies are getting to be eco-conscious, we are called them as ‘green companies’. If these green companies are in one supply chain, we are called as ‘green supply chain’. The coordination of supply chains – whether if traditional or green– is one of the most important research topics in this century. The number of chain members is growing; the cooperation is getting to be more difficult. That is why contracts could be a good solution for this problem, because they define a framework for the parties to manage their relationships. Contracts work well, if the right type is chosen according to the nature of the relationship. But in the case of a green supply chain, there are other influencing factors. Green companies are able to accept higher prices to get higher quality products. In the paper, we analyse how these factors influence the decision-makers to choose between the contracts; we use the AHP decision-making method.